Pengaruh Keselamatan Dan Kesehatan Kerja Terhadap Produktivitas Kerja - Jogi Sinaga; Rimmar Siringo-Ringo; Meiliyani Br Ginting (JEMA: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The study aims to investigate the influence of occupational safety and health (OHS) factors on work productivity at PT. TPL Tbk in the Habinsaran sector. The research method uses the inspection method to evaluate the relationship between OHS practices and productivity levels. The results are expected to provide insight for companies about the importance of OHS in improving employee efficiency and welfare. Occupational Safety and Health (OHS) is a crucial aspect in the manufacturing industry, including in the pulp and paper industry. PT. Toba Pulp Lestari, Tbk, a leading company in this sector in Indonesia, has shown a strong commitment to implementing OHS in its production activities. The report observes the implementation of OHS implemented by TPL with a focus on risk assessment and control, training and education, use of personal protective equipment (PPE), and programs that have been carried out. The LP&C (Loss Prevention & Control) Department is part of a company that aims to maintain business profits by reducing losses due to theft, fraud or operational errors that are periodically monitored routinely on each worker to prevent unwanted accidents. Thus, the company can design appropriate control measures to reduce risk to an acceptable level. In addition, training and education on K3 are held comprehensively for all employees. This aims to ensure that all workers understand the potential hazards in the workplace and know how to protect themselves. Occupational Safety and Health Management System, that: Occupational Safety and Health Management System is part of the overall management system that includes organizational structure, planning, responsibility, implementation, procedures, processes and resources needed for the development, implementation, achievement, assessment and maintenance of occupational safety and health policies in order to control risks related to work activities in order to create a safe, efficient and productive workplace.